The instability of a flow in an inclined alluvial channel - Hung, Pham (Vietnam Journal of Mechanics, 1990)
The instability of a flow in an inclined alluvial channel is investigated by the characteristic and the Fourier methods. It is shown that the bed form development could influence significantly on the stability of the water surface.